Moderate-intensity statin therapy. Efficacy and safety issues - N. G. Gogolashvili (Российский кардиологический журнал, 2023)
High rates of cardiovascular (CV) morbidity and mortality dictates the need to determine approaches to therapy that would reduce complications rate and improve patient’s prognosis. High-intensity statin therapy is an integral part of the treatment of patients with high and very high cardiovascular risk. At the same time, there is a large cohort of patients who would benefit from moderate intensity statin therapy. In the present article we have summarized available data on hypolipidemic effects, pleiotropic effects and role of moderate intensity statin therapy, atorvastatin particularly, in reding the risk of major adverse cardiac events.